Comparative phytochemical screening and antioxidant activity of lemon grass and sweet wormwood leaves extract - R, Murtala; S. I., Alhassan; H.I, Rasheed; S. N., Dalhatu; S.S, Bala; S.A, Idris; D. C., Anyanaso (International Journal of Advanced Chemistry, 2021)
Sweet wormwood (Artemisia annua) and lemongrass (Cymbopogon citratus) leaves were extracted with methanol, evaporated to dryness and processed for antioxidant activity and phytochemical screening. Phosphomolybdenum Reagent was prepared using standard procedure. An aliquot mixture of 2mL of extract solution (1000Âµg/mL, 500Âµg/mL, 250Âµg/mL, 125Âµg/mL, 62.5Âµg/mL, 31.25Âµg/mL and 15.625Âµg/mL) was mixed with 1.8mL of reagent solution. The samples tubes were incubated at 95Â°C for 90 minutes. The absorbance of the aqueous solutions was measured at 695nm against blank. Antioxidant activities of the plants extract were also measured in terms of hydrogen donating radical scavenging ability using the stable DPPH method. Absorbance was recorded at 517 nm against blank using a UV-Vis spectrophotometer. The result of in vitro antioxidant potential of the methanolic leaves extract showed more increase in concentration the higher the absorbance. Qualitative Phytochemical Analysis of Lemon Grass and Sweet wormwood shows the presence of phytochemical in lemongrass and sweet wormwood such as flavonoid, tannin, steroid, saponins and cardiac glycoside.Â Â